Dynamic Governance in Accelerating Stunting Reduction: A Study on Local Policy Implementation and the Use of Digital Platforms in Sumedang Regency, West Java - Wahidah, Idah; Sulastri, Rini (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the role of dynamic governance in accelerating stunting reduction in Sumedang Regency, West Java, with a focus on the mechanisms of sensing, seizing, and transforming as well as the orchestration of multi-actor collaboration. This research is important because stunting remains a critical challenge for Indonesia in achieving the 14% target by 2024, while existing studies are mostly dominated by medical and nutritional perspectives rather than governance aspects. The study employed a qualitative research approach with a case study design, in which data were collected through in-depth interviews, Focus Group Discussions (FGDs), participatory observation, and document analysis. The findings reveal that Sumedang possesses strong dynamic governance capabilities: (1) sensing through data-driven policies utilizing Riskesdas and e-PPGBM, (2) seizing through adaptive regulations and cross-sectoral coordination with Regent Regulation No. 82/2018 and the implementation of the Eight Convergence Actions, and (3) transforming through institutional innovation with the SIMPATI platform and the establishment of a permanent stunting task force. These capabilities are strengthened by the collaborative roles of local government, NGOs, village administrations, health cadres, and the private sector. The integration of digital governance and participatory mechanisms has enabled Sumedang to successfully reduce stunting prevalence from 32.2% in 2019 to 27.6% in 2022, and further to 7.89% in 2023. The implications of this study affirm that dynamic governance can serve as a replicable model for other regions to overcome bureaucratic rigidity, strengthen cross-sectoral partnerships, and enhance evidence-based decision-making in public health policy. The originality of this research lies in positioning stunting reduction not merely as a health intervention but as an innovation in adaptive governance, thereby filling the gap in the literature that rarely discusses the intersection of governance, technology, and community participation in public health policy.